Growth hacking as an approach to producing growth amongst UK technology start-ups: an evaluation. Issue 2 (16th December 2019) - Conway, Tony; Hemphill, Tanya
Abstract : Purpose: "Growth hacking" is a "data-informed" marketing approach that uses digital marketing tools and tactics as well as traditional marketing channels to help technology companies show "proof-of-concept" and sustainability before gaining funding. The purpose of this study was to identify and understand the relevance and importance of growth hacking and identify what growth hacking tools and techniques are used by such organisations. Design/methodology/approach: The main research method for the collection of primary data was in-depth interviews with both industry experts (senior professionals working for growth hacking agencies) and individual growth hacking practitioners who work for technology start-ups based in the UK. Interviews included the use of dimension cards with key growth hacking terms to act as visual cues to facilitate focus and prompt reflection. Findings: In addition to a data analysis element, growth hacking also requires people to spot emerging opportunities before anyone else does. This makes it very difficult to find people with the right skill-set. It is also important to use traditional marketing methods to bridge the gap between the physical and digital world. Originality/value: This study shows that growth hacking is a mind-set and process that can help technology start-ups grow quickly with a limited marketing budget. The research offers guidelines and frameworks for start-ups to understand the growth hacking process. The concept has direct synergy with agile marketing and this might be a term/ methodology with which people in the UK may feel more comfortable given the negative connotations of the word "hacking".